Scientific School of Professor E.A. Elenevskaya - T. Yu. Serebryakova (Учёт. Анализ. Аудит, 2025)
The graduates of the Cheboksary Cooperative Institute (branch) of the Russian University of Cooperation have contributed to Professor E. A. Elenevskaya’s scientific school’s recognition in the accounting community of the Chuvash Republic and surrounding areas. Over its lifespan, the program has helped over 2,000 specialists in accounting, control, economic analysis, and auditing launch their careers. Scientific research has enabled economic and accounting specialists in consumer cooperative organizations to use advanced management accounting techniques, contributing to creating scientific methods in business practices. The accounting department faculty at the Cheboksary Cooperative Institute and Chuvash State Agricultural University comprises graduate and doctoral students from Evgenia Anatolyevna’s school. E.A.’s associates and students stand out for their deep study of scientific categories, practical methods, and innovative trends, along with their ability to combine these elements for optimal application of professor Elenevskaya.